Pemahaman Pekerja Muslimah Terhadap Fiqih Thaharah dan Shalat dalam Madzhab Syafi’i - Darwis, Darwis; Mujahidin, Endin; Ibdalsyah, Ibdalsyah (Ta’dibuna: Jurnal Pendidikan Islam, 2013)
Men and women are created by God worship to Allah. In carrying out his duties as a servant of Allah, armed with advice and guidance in order to avoid a number of irregularities and fraud. Nevertheless, there are several things that distinguish between duties and responsibilities between men and women. If the problem wudhu’, tayamum, janabah, and prayer is the same among men and women, then that is different is the issue of menstruation and istihadhah. This study aims to find a variety of issues related to fiqh thaharah and prayers for Muslimah workers and provide a solution to the problem. The approach used in this study is qualitative. The data source is the Muslim workers working in PT. Investama Mandiri genuine, Coventry-Bogor; KPP PMA TWO, Kalibata, South Jakarta; KPP Primary Kebayoran I, Patra Jasa, Central Jakarta; PT.Gunung Agung, Jakarta Centre; Muslim Family Citi Bank, South Jakarta, and KPP PMB, K-Link Tower, Central Jakarta. Results about the perception and understanding of the Muslimah workers in six offices or companies indicated that their perception and understanding of fiqih thaharah and prayers can be said to be good. But regrettably there are two issues related to the knowledge of fiqih thaharah are not understood by the respondents, namely: (1) When the respondent has dried from the menstruation, while they are still working in the office, because it is not available in the office bathroom, they do not pray with unwashed reasons, because there is no bathroom in which to bathe menstruation. And the number of respondents who expressed a very high opinion, 88.25%, (2) the respondents also thought that after they shower menstruation, then there is "something" out of their genitalia yellowish, or brownish, and are part of the blood of menstruation, finally they are not praying, because it was considered that menstruation not dry. Conditions of respondents who express an opinion as much as 69.67% over. Keywords: Fiqih Thaharah, Madzhab Syafi’i, Pemahaman, Pekerja Muslimah